Bone remodeling in type 1 diabetes mellitus - S. S. Safarova (Бюллетень сибирской медицины)
The aim of the study is to assess the effect of changes in the body in men and women with type 1 diabetes on the state of bone mineral density and metabolic rate and determine the directionality of changes in serum markers of bone remodeling and bone mineral density in both sexes with this disease.Materials and methods. Bone mineral density (with (DXA) and serum bone remodeling markers [ALP, P1NP and b-CTx] were measured in 57 women and 41 men with type 1 diabetes (n = 98) and in a group control, consisting of 43 women and 39 men (n = 82).Results. Analysis of the obtained results showed lower values in all the surveyed areas in patients with diabetes, compared with the control group. It was found that the studied bone formation markers (ALP, P1NP) behave differently; while the P1NP level is significantly reduced in women with T1DM vs control patients (p < 0.001), the level of ALP was comparable between the groups of patients with T1DM and control (p > 0.05). b-CTx showed a significant negative correlation with the T-score of the MIC of the lumbar spine (r = –0.431; p = 0.000).Conclusions. Based on the results of studying the T-score it was found that in men and women with diabetes, in comparison with the control, the bone density in the vertebrae was reduced. In men with type 1 diabetes changes in the T-score in the spine were found to be less intense than in women.